(untitled) - Asadi, Mosen (Hoboken, N.J., 2007)
This book is a practical and concise reference for technologists, chemists, farmers, and research personnel involved with the beet-sugar industry. It covers: Basics of beet-sugar technology, Sugarbeet farming, Sugarbeet processing, Laboratory methods of analysis, The book also includes technologies that improve the operation and profitability of the beet-sugar factories
Keywords: Beet sugar,Beet sugar industry,Sugar,Đường,Ngành chế biến đường từ củ cải,Đường củ cải; Manufacture and refining,sản xuất và tinh chế